Which Factors Explain the Rising Ethnic Heterogeneity in Italy? An Empirical Analysis at Province Level - Cristina Cattaneo (Fondazione Eni Enrico Mattei (FEEM), 2014)
The paper investigates the determinants of ethnic heterogeneity of the Italian provinces. Among other factors, the paper tests empirically whether gradual improvements in distant communication boost the generation of ethnically heterogeneous provinces. Consequently to easier communication, movers increasingly rely on an enlarged community for identity transmission, rather than on localized peer effects of the ethnic enclaves. The empirical estimation provides support to this hypothesis. Improvements in internet communications are found to increase the ethnic diversity of the Italian provinces.
Keywords: F22; J61; R11; 330; Immigration; Ethnic Diversity; Productivity